An emotionally focused workbook for couples : the two of us - Kallos-Lilly, Veronica; Fitzgerald, Jennifer Robyn, 1957- (New York : Routledge, 2015)
"This workbook is intended for use with couples who want to enhance their emotional connection or overcome their relationship distress. It is recommended for use with couples pursuing Emotionally Focused Therapy (EFT). It closely follows the course of treatment and is designed so that clinicians can easily integrate guided reading and reflections into the therapeutic process. The material is presented in a recurring format: Read, Reflect, and Discuss. Readings help couples look at their relationship through an attachment lens, walking them through the step-by-step process of creating a secure relationship bond. 33 Reflections invite readers to engage with the material personally, expanding their own awareness and ability to tune into their partner. Discussion sections suggest relationship-building exercises and a framework for conversations that promote safety, disclosure, and engagement. Case examples, along with informative illustrations, are scattered throughout the book to validate, illustrate, and inspire couples along their journey. Clinicians conversant with EFT can use this workbook to extend the effectiveness of their work with couples by giving them structured tasks to work on between sessions. For clinicians training in EFT, the book can guide them in staying focused on the EFT roadmap and illuminate how important change events unfold"--
Introduction : who is this book for? -- What happened to us? Three cycles of relationship distress -- Attachment bonds : the best chance of survival -- My partner and me : what influenced who we are and how we are in close relationships? -- Emotions : how to make sense of them -- More about emotions : what are we both feeling? -- More difficult emotions : contempt, hurt, shame, guilt and jealousy -- The road to security is paved with good intentions -- Rebuilding our bond -- Relationship injury : how can we repair the damage? -- Stories of change -- Maintaining intimacy and revitalizing your sex life -- Looking ahead : anticipating life transitions -- Final words.
Keywords: Man-woman relationships; Marital psychotherapy; Emotion-focused therapy; Interpersonal relations; Attachment behavior; PSYCHOLOGY / Psychotherapy / Couples & Family; PSYCHOLOGY / Mental Health